The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1094/pdis-10-19-2128-re
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Pathogens Associated With Canker Diseases of Almond in California

Abstract: Almond canker diseases are destructive and can reduce the yield as well as the lifespan of almond orchards. These diseases may affect the trunk and branches of both young and mature trees, and in severe cases can result in tree death soon after orchard establishment. Between 2015 and 2018, 70 almond orchards were visited throughout the Central Valley of California upon requests from farm advisors for canker disease diagnosis. Two major canker diseases were identified including Botryosphaeriaceae cankers and Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 46 publications
1
30
1
Order By: Relevance
“…The fungus shows a large geographic distribution worldwide. For instance, it has been isolated from almond trees showing symptoms of band canker in California [13,25] and symptoms of dieback in turkey [45]. Further, the pathogenicity experience in this work revealed that the L. theobromae showed the highest virulence on almonds causing a longer lesion of an average of 280 mm; these results were close to previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fungus shows a large geographic distribution worldwide. For instance, it has been isolated from almond trees showing symptoms of band canker in California [13,25] and symptoms of dieback in turkey [45]. Further, the pathogenicity experience in this work revealed that the L. theobromae showed the highest virulence on almonds causing a longer lesion of an average of 280 mm; these results were close to previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, dieback of scaffold branches and shoots through pruning wounds and damaged tissues were reported [12]. Cross section of infected tissues showed circular, irregular, or wedge-shaped necrosis, leading to the destruction of phloem and xylem tissues, and therefore, in the end, canker blocks the circulation of water and nutrients resulting in the death of bark and cambium [13]. In the recent past, numerous studies have been conducted on fungal trunk pathogens of fruit trees, such as stone and pome fruit trees [14][15][16], grapevine [17,18] pistachio [19,20], Ficus trees [21], blueberry [22] and olive [23].…”
Section: Introductionmentioning
confidence: 99%
“…Found primarily in California and Arizona, it remains unclear on what environmental medium Coccidioides primarily grows, its source of nutrition (Barker et al, 2012; Emmons, 1942; Kollath, Teixeira, et al, 2019; Taylor & Barker, 2019), or its precise means and range of dispersal (de Perio et al, 2019; Nicas, 2018; Pappagianis & Einstein, 1978; Schneider et al, 1997; Wilken et al, 2015). Agriculturally, the SJV is the most productive region in the United States (Food & Agriculture (CDFA), 2018), and plant pathogenic and parasitic fungi are responsible for significant losses in many of the chief crops grown therein (Baumgartner et al, 2019; Baumgartner & Rizzo, 2002; Camiletti et al, 2022; Holland et al, 2021). Determining the source and dispersal characteristics of airborne fungi can aid in preventing or mitigating fungal disease in humans and crops as well as offering a better understanding of fungal community ecology.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Botryosphaeriaceae are probably most wellknown as being destructive blight and canker pathogens of planted hosts (Luo et al, 2019). In agricultural settings, for example, they infect a large number of fruit and nut crops, such as almond (Inderbitzin et al, 2010;Gramaje et al, 2012;Nouri et al, 2018;Holland et al, 2020), apple (Phillips et al, 2012), avocado (McDonald et al, 2009), citrus (Linaldeddu et al, 2015), grapevine (Urbez-Torres, 2011), olive (Úrbez-Torres et al, 2013), pistachio (Michailides, 1991;Nouri et al, 2019), and walnut . In forest plantations in Australia and South Africa, for example, they infect Eucalyptus spp.…”
Section: Introductionmentioning
confidence: 99%